(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Education in general and higher education in particular play an important role in shaping the national knowledge economy. For effective management of the development of higher education in general and higher education institutions in particular, it is advisable to diagnose in what condition they are today and predict their condition in the future. The purpose of the article is to form a system of methods of analysis and forecasting of key areas of higher education in Ukraine. Results. The first stage of the methodology of complex diagnostics of development and efficiency of management of higher education of Ukraine «Analysis of development of higher education in Ukraine» provides the decision of three consecutive tasks: the analysis of system of higher education in Ukraine; analysis of scientific and innovative development of Ukraine in the regional context; analysis of financial and investment support for the development of higher education. The second stage «Analysis of the effectiveness of management of higher education in Ukraine» consists of three consecutive tasks: analysis of the effectiveness of management of educational, scientific and financial components of higher education. The third stage «Forecasting the development of higher education in Ukraine» involves solving the following tasks: modeling the development of educational and scientific components of higher education, financial and investment support for its development. The fourth stage «Development of strategic directions for the development of higher education in Ukraine» consists of three consecutive tasks: educational and social, scientific and innovative, financial and investment areas for the development of higher education. Conclusions. It is proposed to conduct a comprehensive diagnosis of the development and effectiveness of higher education management in Ukraine at the macro and micro levels, analyzing its key areas of activity (educational, scientific, financial and investment) using the following methods: SWOT-analysis, component analysis, critical path, decision tree, ABC-analysis, trend extrapolation, cluster analysis, construction of an integrated exponent, fuzzy sets, probabilistic-automatic modeling.